Atividade antifúngica do ácido elágico contra Candida de interesse clínico - MENDES, Amanda Graziela Gonçalves (2024)
Antifungal resistance to azoles, the limitation of distinct classes of antifungals, together with the increase in Candida infections, represent a significant challenge for public health, which has driven the search for new compounds with antimicrobial action as an alternative to this problem. Phenolic compounds are natural products from plants that can act as adjuvants to conventional antifungals. Ellagic acid (EA) is a naturally occurring dietary phenolic compound derived from gallic acid that has been reported with antifungal activity, but its effects in association with fluconazole (FLZ), a drug used to treat candidiasis, are not yet fully understood. The aim of this study was to investigate the in vitro anti-Candida activity of EA and its ability to potentiate the effects of FLZ. The Minimum Inhibitory Concentration (MIC) was determined by broth microdilution and its interaction with FLZ was evaluated using a checkerboard assay. Furthermore, we examined the effects of AE on time-kill kinetics, yeast- to-hypha transition, inhibition of biofilm formation, hemolytic activity, and cytotoxicity in HeLa ATCC ® CCL-2TM cells. AE exhibited MIC values ranging from 250 to 2000 μg/mL and showed synergistic and additive interactions with FLZ, resulting in a marked reduction in the MIC values of FLZ (up to 32-fold) and EA (up to 16-fold). In the time-kill assay, the most effective combinations were 4× AE MIC, 2× AE MIC, and 4× and 2× CIF AE + FLZ, which showed fungicidal activity. Furthermore, AE showed no hemolytic activity and demonstrated low and dose-dependent cytotoxicity in HeLa cells, with no cytotoxic effects observed in combination with FLZ. AE and the synergistic combination of AE and FLZ interfered both in the yeast-to-hypha transition process and in biofilm formation. In addition to its antifungal activity, AE presented a favorable safety profile at the concentrations evaluated. The results obtained indicate a great potential for the use of AE in combination with FLZ in the treatment of Candida infections.